Chevron osteotomy with minimally invasive surgery (MIS) of the first metatarsal. - Jorge Javier del Vecchio; Mauricio Esteban Ghioldi; Nicolás Raimondi (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2017)
Background